KUALITAS PELAYANAN, PENGALAMAN PELANGGAN DAN CAFÉ ATMOSPHERE SERTA PENGARUHNYA TERHADAP KEPUASAN PELANGGAN KONSUMEN KOPI KENANGAN NGAGEL SURABAYA - Ariyanto, Mahira Putri; Santoso , Rudy (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of Service Quality, Customer Experience, and Café Atmosphere on Customer Satisfaction at Kopi Kenangan Ngagel Surabaya. Employing a quantitative approach with purposive sampling, 100 consumers participated in the study. Data analysis utilized SPSS 26.0, including instrument testing (validity and reliability), classical assumption testing (normality, multicollinearity, and heteroscedasticity), multiple linear regression, and hypothesis testing (T-test and F-test). Results indicate that Service Quality and Café Atmosphere significantly impact Customer Satisfaction, while Customer Experience does not. Simultaneously, all independent variables (Service Quality, Customer Experience, and Café Atmosphere) significantly influence Customer Satisfaction).